Revision of existing classification of fossil insect feeding traces and description of new ichnotaxa from Middle Jurassic sediments of Eastern Siberia (Russia) - Enushchenko, Ilya V.; Frolov Аndrey O. (Zootaxa, 2020)
This paper revises the existing system of formal classification by Vialov and Vasilenko for fossil plants involving insect feeding and oviposition. The classification of these fossil traces has been amended and supplemented in accordance with the requirements of the International Code of Zoological Nomenclature. The following nomenclatural combinations are made: Insectophagichnata (Vialov) Enushchenko and Frolov, comb. et stat. (classis) nov., Phagolignichnidina (Vialov) Enushchenko and Frolov, comb. et stat. (subordo) nov., Phagophytichnidina (Vialov) Enushchenko and Frolov, comb. et stat. (subordo) nov. Fossil traces of these interactions were found and illustrated for Mesozoic insects and leafes of Ginkgo tapkensis from Middle Jurassic sediments of the Irkutsk Coal Basin in Eastern Siberia, Russia. The examined traces consist of ovipositions (traces of insect egg laying), galls (traces of insect caused teratologies) and epidermal punctures (traces of piercing and sucking). The following ichnotaxa are described and illustrated: Paleoovidinae Enushchenko and А. Frolov, ichnosubfam. nov., Paleoexoovoidinae Enushchenko and Frolov, ichnosubfam. nov., Sugophytichninae Enushchenko and А. Frolov, ichnosubfam. nov., Sugophytichnida pertusura Enushchenko and Frolov, ichnogen. et ichnospec. nov., Paleoovidus vasilenkoi Enushchenko and А. Frolov, ichnospec. nov., Paleoexoovoida ovoidea Enushchenko and А. Frolov, ichnogen. et ichnosp. nov., Paleogallus vialovi Enushchenko and Frolov, ichnospec. nov. Punctures of the leaf epidermis probably belong Mesozoic cicadas of the Palaeontini, which dominate the adjacent strata of the studied location. The extremely low occurrence of interaction between insects and plants in these Jurassic deposits of Eastern Siberia have ichnotaxonomic importance for understanding the functioning of Jurassic terrestrial paleoecosystems.